A research agenda for augmented and virtual reality in architecture, engineering and construction. (August 2020) - Davila Delgado, Juan Manuel; Oyedele, Lukumon; Demian, Peter; Beach, Thomas
Abstract: This paper presents a study on the usage landscape of augmented reality (AR) and virtual reality (VR) in the architecture, engineering and construction sectors, and proposes a research agenda to address the existing gaps in required capabilities. A series of exploratory workshops and questionnaires were conducted with the participation of 54 experts from 36 organisations from industry and academia. Based on the data collected from the workshops, six AR and VR use-cases were defined: stakeholder engagement, design support, design review, construction support, operations and management support, and training. Three main research categories for a future research agenda have been proposed, i.e.: (i) engineering-grade devices, which encompasses research that enables robust devices that can be used in practice, e.g. the rough and complex conditions of construction sites; (ii) workflow and data management; to effectively manage data and processes required by AR and VR technologies; and (iii) new capabilities; which includes new research required that will add new features that are necessary for the specific construction industry demands. This study provides essential information for practitioners to inform adoption decisions. To researchers, it provides a research road map to inform their future research efforts. This is a foundational study that formalises and categorises the existing usage of AR and VR in the construction industry and provides a roadmap to guide future research efforts.